MANAJEMEN NYERI - Adji Mustiadji (Yayasan Nusantara Hasana Berdikari, 2026)
Pain management is a critical component of healthcare services aimed at reducing patient suffering, improving quality of life, and promoting recovery. Effective pain management requires a comprehensive assessment using standardized tools to identify the intensity, location, duration, and characteristics of pain. Management strategies involve both pharmacological and non-pharmacological approaches. Pharmacological interventions include the administration of analgesics, such as nonsteroidal anti-inflammatory drugs (NSAIDs), opioids, and adjuvant medications, tailored to the patient's condition and pain severity. Non-pharmacological methods, including relaxation techniques, distraction, music therapy, cognitive-behavioral interventions, and physical therapies, can complement medical treatment and enhance pain relief. Furthermore, multidisciplinary collaboration among physicians, nurses, pharmacists, and other healthcare professionals plays a vital role in ensuring effective and safe pain management. Continuous monitoring and patient education are also essential to optimize treatment outcomes and prevent complications associated with uncontrolled pain. Effective pain management contributes significantly to patient satisfaction, functional recovery, and overall healthcare quality.